1996
DOI: 10.1074/jbc.271.11.6039
|View full text |Cite
|
Sign up to set email alerts
|

In Murine 3T3 Fibroblasts, Different Second Messenger Pathways Resulting in the Induction of NO Synthase II (iNOS) Converge in the Activation of Transcription Factor NF-κB

Abstract: Transcription factor NF-B is essential for the induction of nitric oxide synthase (NOS) II (iNOS) by bacterial lipopolysaccharide in murine macrophages (Xie, Q. W., Kashiwabara, Y., and Nathan, C. (1994) J. Biol. Chem. 269, 4705-4708). In 3T3 fibroblasts, agents other than cytokines are efficacious inducers of NOS II expression. In addition to cytokines such as interferon-␥ or tumor necrosis factor-␣, protein kinase C-stimulating agents such as tetradecanoylphorbol-13-acetate, or cyclic AMPelevating agents suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
79
0
3

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 56 publications
2
79
0
3
Order By: Relevance
“…In this study, we have demonstrated that NF-B inhibitors abrogate SDF1␣-induced chemotactic effects. NOrelated compounds have been shown to activate NF-B activity (42). Moreover, the transcriptional activity of NF-B has been shown to regulate iNOS gene expression (68,69).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have demonstrated that NF-B inhibitors abrogate SDF1␣-induced chemotactic effects. NOrelated compounds have been shown to activate NF-B activity (42). Moreover, the transcriptional activity of NF-B has been shown to regulate iNOS gene expression (68,69).…”
Section: Discussionmentioning
confidence: 99%
“…NF-B has been shown to influence NO production by regulating expression of the inducible NO synthase gene (42). Conversely, NO has also been shown to be capable of modulating NF-B function in mononuclear leukocytes and endothelial cells (43,44).…”
mentioning
confidence: 99%
“…Such as, cAMP induces the expression of iNOS in LPS-and cytokine-stimulated glomerular mesangial cells (Muhl et al, 1994), vascular smooth muscle cells (Koide et al, 1993), cardiac myocytes (Ikeda et al, 1996), murine 3T3 fibroblasts (Kleinert et al, 1996) and rat peritoneal macrophages (Sowa and Przewlocki, 1994). In these studies, the increase in cAMP level resulting due to inhibition of phosphodiesterase (an enzyme that degrades cAMP), or due to an exogenous input of cAMP derivatives or compounds that enhance intracellular levels of cAMP, induce and/or stimulate iNOS expression.…”
Section: The Camp In Glial Inos Regulation: Unique Regulation By Campmentioning
confidence: 99%
“…6 Furthermore, inhibition of viral replication by NO is shown by many laboratories by using NO donors, inhibiting NO production by NOS-inhibitors, or by using iNOS knockout mice. 7 To induce iNOS messenger RNA (mRNA), activation of the transcription factor nuclear factor-B (NF-B) is essential [8][9][10][11][12] although probably not sufficient 13,14 for full iNOS induction. To induce gene transcription, NF-B must be translocated from the cytoplasm to the nucleus.…”
mentioning
confidence: 99%